Pregnant Women's Experiences Using a Mobile Application for Iron Supplementation Adherence: A Phenomenological Approach - Dewi, Arlina; Wirasto, Anggit; Dewi, Trisna Setya (Unnes Journal of Public Health, 2024)
Iron deficiency anemia is a significant global public health concern that disproportionately affects young children and pregnant women. One effective method for monitoring medication in pregnant women is through mobile applications. This study aims to investigatepregnant women’s experience with iron supplementation adherence management using amobile application. A qualitative study with a phenomenology approach was conductedamong 20 pregnant women and midwives. The qualitative method was used to explore participants’ experience using a maternal application called “MySmart Bumil” to improvepregnant women’s adherence to iron supplements. The study identified four themes: the factors of non-compliance, the motivation for taking iron supplements, and the benefits andthe weaknesses of using the application. Mobile app reminders can help pregnant womencheck medication frequency, remind them to take iron tablets, and build more consistentmedication habits. However, some pregnant women found that the reminder was ineffective. Pregnant women thought that the notifications should have alarms to be more effective. The mobile application has the potential to assist health providers in effectively monitoring the health state of pregnancy and improving adherence to iron supplementation